Hubungan antara Kecemasan dengan Frekuensi Bangkitan pada Penderita Epilepsi Parsial di RSUD Dr. Moewardi - Lucia Pancani Anggraeni; Diah Kurnia Mirawati; Endang Sutisna Sulaeman (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Anxiety is a psychological disorder that involves dysregulation of the nervous system Therefore, anxiety could affected seizures threshold in people with epilepsy indirectly. The aim of this study was to know an association between anxiety and seizure frequency of partial epileptic patients in hospitals Dr. Moewardi. Methods: This was an observational study with analytic cross sectional approach. Samples were taken by purposive sampling after selected based on inclusion and exclusion criteria. The data were obtained by using of TMAS anxiety scale, interviewed seizures frequency in last one month, and the patient's medical record. Analysis of anxiety and seizures frequencys score used linear regression models by SPSS 17.0 for windows Results: There were 31 samples consisted of 10 women and 21 men. Result showed a significant positive relation between anxiety and seizure frequency of partial epileptic patients in hospitals Dr. Moewardi (p < 0.05, CI 95% = 0.06 - 0.037). Linear regression analysis test showed an equation that Y= a + bX = -1.174 + 0.218 X. It meaned that the seizure frequency would rise -1.174 + 0.218 X unit for every inrcreasing of anxiety level. Conclusion: Patients with higher level of anxiety have had more often seizure attack. Keywords: Partial epileptic patients, anxiety, frequency of seizure